Discs to a 'Bright' Future: Exploring Discotic Liquid Crystals in Organic Light Emitting Diodes in the Era of New‐Age Smart Materials. Issue 8 (20th May 2022) - De, Ritobrata; Sharma, Sushil; Sengupta, Sanchita; Kumar Pal, Santanu
Abstract: With the advent of a new decade and the paradigm shift of every sphere of urban life to virtual platforms, it has become imperative for the global researcher community to channelize efforts into upgradation of the existing display‐technology. In this context, discotic liquid crystals (DLCs) are a class of self‐assembling organic materials that are recently being explored in fabricating the emissive layers of organic light emitting diodes (OLEDs). With their unique inherent structural and functional properties, they have the potential to challenge the currently prevailing OLED‐emitters. Yet the applications of this promising class of materials in OLEDs have not been comprehensively reviewed in literature till now. In this account, we present an overview of the developments in the field of luminescent DLC‐based emitters, supported by their associated photophysical phenomena and their performance parameters as emitters in fabricated OLED devices. Abstract : This account outlines the evolution of Discotic Liquid Crystals (DLCs) as emitters in organic light‐emitting diodes (OLEDs) through varied photophysical processes like fluorescence, aggregation‐induced emission (AIE), and hybrid local and charge transfer (HLCT). The efficiency of these self‐assembling molecules is also discussed in terms of device parameters for OLED devices fabricated with representative examples.